Benefits of Irrigation or Fertigation on Early Growth and Yield of a High-density Apple Planting in a Humid Climate - Leo I. Dominguez; Terence L. Robinson (HortTechnology)
The success of a new high-density apple planting depends on how fast the grower can recoup the high investment that these systems require. The right balance between vegetative growth and cropping during the early life of the planting is where tree growth is sufficient to rapidly fill the allotted space while at the same time producing high early yields. In this study we evaluated irrigation or fertigation as strategies compared with the traditional nonirrigated control to improve growth and yield of five apple scion cultivars (Mutsu, Gala, Honeycrisp, Jonagold, and Macoun) on M.9 or B.9 rootstocks over the first 5 years at Geneva, NY. Calcium nitrate at the rate of 113 kg·ha−1 N was applied to all three irrigation treatments (dissolved in water for the fertigation treatment, broadcast dry with the irrigation treatment, or broadcast dry with the nonirrigated control). Our results showed that fertigation with dissolved N and irrigation with dry broadcast N increased yield and tree growth similarly and significantly over the first 5 years of orchard establishment compared with the nonirrigated treatment with dry broadcast N. There was a significant economic benefit of irrigation or fertigation in the humid climate of New York State.